Developmental mapping of small‐conductance calcium‐activated potassium channel expression in the rat nervous system. Issue 5 (1st April 2014) - Gymnopoulos, Marco; Cingolani, Lorenzo A.; Pedarzani, Paola; Stocker, Martin
Abstract Early electrical activity and calcium influx regulate crucial aspects of neuronal development. Small‐conductance calcium‐activated potassium (SK) channels regulate action potential firing and shape calcium influx through feedback regulation in mature neurons. These functions, observed in the adult nervous system, make them ideal candidates to regulate activity‐ and calcium‐dependent processes in neurodevelopment. However, to date little is known about the onset of expression and regions expressing SK channel subunits in the embryonic and postnatal development of the central nervous system (CNS). To allow studies on the contribution of SK channels to different phases of development of single neurons and networks, we have performed a detailed in situ hybridization mapping study, providing comprehensive distribution profiles of all three SK subunits (SK1, SK2, and SK3) in the rat CNS during embryonic and postnatal development. SK channel transcripts are expressed at early stages of prenatal CNS development. The three SK channel subunits display different developmental expression gradients in distinct CNS regions, with time points of expression and up‐ or downregulation that can be associated with a range of diverse developmental events. Their early expression in embryonic development suggests an involvement of SK channels in the regulation of developmental processes. Additionally, this study shows how the postnatal ontogenetic patterns lead to the adult expression map for each SK channel subunit and how their coexpression in the same regions or neurons varies throughout development. J. Comp. Neurol. 522:1072–1101, 2014. © 2013 Wiley Periodicals, Inc.